1981
DOI: 10.3354/meps006123
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Degradation and Efficiency of Conversion of Phytoplankton Debris by Marine Micro-Organisms

Abstract: Detritus from the dinoflagellates Scrippsiella (= Peridinurn) trochoidea and Isochrysis galbana and from the diatoms Skeletonema costaturn, Thalassiosira angstii and Chaetoceros tricornuturn incubated at 10 "C in seawater is colonised by a succession of micro-organisms. Primary microbial decomposers in the incubation experiments were bacterial rods and cocci which reached a peak standing stock carbon of 1.86 f 0.76 % of the carbon supplied to the incubation media by the third day of incubation. The bacteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(60 citation statements)
references
References 29 publications
6
54
0
Order By: Relevance
“…Although this is at the low side of the range generally cited for the growth yield ratio in pure culture or in enriched samples (Williams 19 8 1;Billen 19 84), it is not unrealistic in natural situations where nitrogen deficiency can limit bacterial production. For instance, the data of Lucas et al (1981), Newell et al (1981Newell et al ( , 1983, and Linley et al ( 198 3), who measured directly the production of bacterial biomass from the heterotrophic utilization of various organic materials in seawater, show growth efficiencies in the range of 7-37%.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is at the low side of the range generally cited for the growth yield ratio in pure culture or in enriched samples (Williams 19 8 1;Billen 19 84), it is not unrealistic in natural situations where nitrogen deficiency can limit bacterial production. For instance, the data of Lucas et al (1981), Newell et al (1981Newell et al ( , 1983, and Linley et al ( 198 3), who measured directly the production of bacterial biomass from the heterotrophic utilization of various organic materials in seawater, show growth efficiencies in the range of 7-37%.…”
Section: Discussionmentioning
confidence: 99%
“…(If bacteria grow at a lower efficiency, as implied by some studies, e.g. Newell et al [1981], Bjarnsen [1986], this percentage of PP utilized by bacteria would be even larger.) This value of bacterial production as 20 % of primary production agrees extremely well with Williams' (1981) earlier assessment and with other direct studies of carbon cycling in lakes and marine systems.…”
Section: Implications For Aquatic Food Websmentioning
confidence: 99%
“…Studies of OM mineralization of typical microniche highly reactive material have reported losses of labelled C of 85% over 18 days and 65% over 30 days for carcass and faecal pellets respectively (Lee and Fisher, 1992). For whole phytoplankton debris Newell et al (1981) measured that over 30% of the OM is mineralized within 3 days, with a more refractory fraction (~64%) taking up to 11 days for mineralization. The ranges of rate constants in this work are consistent with these and other observations of rapid OM 7 mineralization in the literature (more examples are discussed in section 3.2 in the context of niche lifetimes).…”
Section: Model Descriptionmentioning
confidence: 99%